The Influence of Energy Performance Certification the Market Value of Residential Buildings. (June 2019) - Tagliabue, L C; Cecconi, F Re; Moretti, N; Dejaco, M C
Abstract: The market value of the physical assets over the time varies as a function of different factors related, for instance, to the correct execution of buildings and systems; the conformity with procedures defined for the use phase of the systems; the implementation of maintenance plan, defined in order to maintain the building and its parts in good conditions. Nevertheless, there is not a clear evidence of how the market value is affected by the energy performance measured by the Energy Performance Certification in Italy. The aim of this research concerns the definition of an assessment methodology of the impact of the energy performance on the market value of assets. The methodology has been developed and tested in a case study on the city of Milan, Italy. At first, an investigation of homogeneous income areas has been carried out, afterwards an analysis of the market values of assets has been done. The results have been integrated in a Geographic Information System and gaps in the market values have been associated to the energy performance. Despite the methodology has still to be refined, it has been demonstrated its validity. To conclude, further parameters representing the energy performance of the buildings could be encompassed in the assessment, in order to achieve a more precise energy profile of the building under analysis.